PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE TIPE THINK PAIR SHARE (TPS) BERBANTUAN CANVA DI KELAS IV.A SDN 13 PAUH KOTA PADANG - Rahmi, Adini; Waldi, Atri; Desyandri, Desyandri; Reinita, Reinita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of grade IV students of SDN 13 Pauh, Padang City, which are influenced by low thinking skills, lack of group participation, suboptimal learning design, and teacher-centered learning. This study aims to describe the improvement of student learning outcomes in Pancasila Education learning using the Think Pair Share Cooperative model. This type of research is Classroom Action Research (CAR) with qualitative and quantitative approaches implemented in two cycles. Data were obtained from planning, implementation, and student learning outcomes through test and non-test techniques. The research subjects consisted of 27 students of class IV.A. The results showed an increase in student learning outcomes in cycle I from an average of 78.11 to 91.18 in cycle II. Thus, the Think Pair Share model is proven to improve student learning outcomes.